Genetic spectrum and characteristics of autosomal optic neuropathy in Korean: Use of next-generation sequencing in suspected hereditary optic atrophy - Seo, Yuri; Kim, Tae Young; Won, Dongju; Shin, Saeam; Choi, Jong Rak; Lee, Seung-Tae; Lee, Byung Joo; Lim, Hyun Taek; Han, Sueng-Han; Han, Jinu (Frontiers in Neurology, 2022)
Aims: To evaluate the clinical characteristics and causative genetic variants in autosomal optic atrophy diagnosed using next-generation sequencing (NGS). Methods: A cohort of 57 unrelated families affected with bilateral optic atrophy were recruited from two university-based tertiary referral hospitals from May 2016 to April 2022. Genetic variants were detected using a target enrichment panel consisting of 429 or 595 genes and known deep intronic variants associated with inherited eye diseases, exome sequencing, or genome sequencing. The results of detailed clinical examinations, disease-causing variants, and clinical diagnoses were analyzed. Results: Among the 57 probands, 33 (57.9%) were men, and the median age at genetic testing was 19.1 years (interquartile range, 7.6–42.5 years). We identified 22 likely causative variants in 18 families and corresponding diagnostic yields of 31.6% (95% confidence interval, 21.0–44.5%). The diagnostic rate of NGS was higher in patients with infantile or early childhood onset optic atrophy than in those with late-onset or unknown optic atrophy (16/36, 44.4% vs 1/17, 5.9%, P=0.005). Among the 22 variants, 15 were novel in our cohort. The OPA1 variants (n=7) were found to be the major genetic causes, followed by the NR2F1 variant (n=4). The causative variants in PTPN23, TMEM126A, NBAS, and WFS1 genes were identified in 4 probands with a recessive form of optic atrophy. Conclusions: Based on the results of diagnostic NGS for optic atrophy, the causative variant could be detected in 31.6% of patients. Our study also demonstrated that NGS is unlikely to help identify molecular causes in late-onset unexplained optic atrophy.